At sea with disability! Transformative learning in medical undergraduates voyaging with disabled sailors. Issue 8 (August 2016) - Thompson, Trevor; Lamont‐Robinson, Catherine; Williams, Val
Abstract : Context: Attitudinal objectives are difficult to formulate, teach and assess; yet good attitudes are fundamental to good practice. For instance, studies highlight negative attitudes to disability in the medical student community that contrast with the self‐conceptions of disabled persons. This study was designed to better understand attitudinal learning, inadequately addressed by contemporary programmes, through the application of Mezirow's 'transformative learning theory' (TLT) to a novel educational intervention. Methods: Participating students went to sea, for voyages of 5–7 days, in tall ships operated by the Jubilee Sailing Trust. Each student was buddied with another sailor living with disability. Disabilities included cerebral palsy, loss of sight, loss of limbs and paraplegia. Students recorded their experiences using audio diaries, written logs, formal voyage reports and art work and in post‐voyage seminars. The data were analysed using interpretive phenomenological analysis, and the results are considered under five themes suggested by Mezirow. Results: Sixteen students were recruited, with four students sailing on each of four separate voyages. Each student recorded audio‐diary entries, which had a total duration of between 10 and 212 minutes. For seven of the 16 students, the five key elements of TLT were demonstrable, suggesting that transformative learning, as described by Mezirow, was occurring. Drawing on diverse qualitative data, insights into different aspects of this transformation are provided. Conclusions: TLT can be used to characterise, and thus design, educational interventions to meet attitudinal learning objectives. Students can be helped to discover their less helpful frames of reference. In safe environments these frames can be challenged and subjected to personal and communal reflection. Drawing on audio diaries and other evidence, and in answer to critiques of contemporary medical teaching on disability, we demonstrate such transformation in students 'at sea with disability', highlighting elements that could potentially be transferred to the mainstream curriculum. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.